Knowledge and Awareness of Biomedical Waste Management in The Field of Dentistry - Lastati, Lastati (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Activity service health in practice doctor tooth produce waste medical can give rise to problem Serious If No managed with Good. Waste This own potency fot transmit agent infectious to human, so its management must done in a way carefully and appropriately with correct procedure. Study This use method literature review with narrative review approach. Secondary data used originate from published articles and journals between 2014 to 2024 and can accessed in form fulltext through the PubMed and Google Scholar databases. Appropriate article with criteria inclusion analyzed For compile conclusions and interpretations about knowledge and awareness to management waste biomedicine in field medical tooth. Study results show that knowledge and awareness about management waste biomedicine among practitioner medical tooth Still not enough adequate. Many houses sick and clinic still throw away waste medical with no way right, contributing to the spread disease infectious. Research also highlights importance education and training for officer health tooth in manage waste medical. Required integration curriculum management waste biomedicine in schools medical tooth as well as supervision strict from government for ensure management safe and effective waste. This matter important For protect health society and environment.